Stannathianes as activated polythiols for the synthesis of functionalized macrocyclic polythiolactones. Issue 15 (12th April 2017) - Delgado Espinosa, Zuly Y.; Erben, Mauricio F.
Graphical abstract: Highlights: New stannadithianes are prepared and characterized. Stannadithianes act as activated thiols in the templates synthesis of thiolactones. Novel macrocyclic thiolactones bearing functional groups are prepared. Spirotetrathiolactones of controlled size can be obtained. Abstract: We synthesized novel macrocyclic dithiolactones bearing endocyclic ether, polyether and lactone groups using new stannadithianes as tin templates in the condensation reaction with acid dichlorides and demonstrated an extension of this method toward synthesizing spirotetrathiolactones of controlled size. The structures of all synthesized compounds were characterized by spectroscopic methods.